2010
DOI: 10.1007/s00421-010-1687-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance and physiological responses to repeated-sprint exercise: a novel multiple-set approach

Abstract: We investigated the acute and chronic responses to multiple sets of repeated-sprint exercise (RSE), focusing on changes in acceleration, intermittent running capacity and physiological responses. Ten healthy young adults (7 males, 3 females) performed an incremental test, a Yo-Yo intermittent recovery test level1 (Yo-Yo IR1), and one session of RSE. RSE comprised three sets of 5 × 4-s maximal sprints on a non-motorised treadmill, with 20 s of passive recovery between repetitions and 4.5 min of passive recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 42 publications
6
59
0
3
Order By: Relevance
“…Soccer players complete many direction changes during a match (Bloomfield et al, 2007), and frequent accelerations and decelerations combine to stress the anaerobic capacity of players (Serpiello et al, 2011). This was a feature of the SST drill design from this study (Figure 1).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Soccer players complete many direction changes during a match (Bloomfield et al, 2007), and frequent accelerations and decelerations combine to stress the anaerobic capacity of players (Serpiello et al, 2011). This was a feature of the SST drill design from this study (Figure 1).…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, an important physiological trait of successful soccer players is RSA, as this encompasses the capability to repeatedly perform repeat short high-intensity sprints , Dellal et al, 2010, Serpiello et al, 2011. A number of studies have examined the RSA of team sport athletes, using maximal sprint efforts lasting approximately 5 s, interspersed with recovery periods between 40-56 s (Bishop et al, 2001, Fitzsimmons et al, 1993, Impellizzeri et al, 2008, Spencer et al, 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serpiello et al (96) have recently shown that CaMKII phosphorylation increased 69% after an acute repeated sprint exercise. We (99) have previously reported a marked increase in CaMK autonomous activity and CaMK phosphorylation in rats after exercise.…”
Section: Mechanism Of Camk Activation In Skeletal Muscle During Exercisementioning
confidence: 99%
“…Mean power, peak power and peak velocities during the exercise protocol were recorded 8 by the treadmill force transducer at 25 Hz. Performance data were stored and analyzed as 141 described previously (Serpiello et al 2011 The knee extension protocol used has been described in detail elsewhere (Billaut et al 2013). …”
mentioning
confidence: 99%